Accounting information system user satisfaction: a survey of Indonesian state-owned banks - Kesuma, Sambas Ade; Saidin, Siti Zabedah; Ahmi, Aidi (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2017)
The objective of this study is to explore accounting information system user satisfaction, particulary, this study examines the level of accounting information system user satisfaction among state-owned banks in Indonesia. User satisfaction is generally used as a proxy for the successful implementation of an information system. The findings show that users are satisfied with the implementation of accounting information system. Specifically, majority of respondents indicate their satisfaction in terms of the content, accuracy of the system, format of the information, ease of use of the system, and timeliness of the accounting information system among the Indonesian stateowned banks. Thus, the management of state-owned banks in Indonesia are expected to maintain the good accounting information systems and improve the quality of the systems in order to achieve excellent services and further enhance the operations of the Indonesian state-owned banks.